A case of central odontogenic fibroma of the mandible in a nevoid basal cell carcinoma syndrome patient. Issue 2 (1st February 2018) - Shimada, Yasuyuki; Kawasaki, Yohei; Tayama, Michita; Kindaichi, Junko; Maruoka, Yutaka
Abstract: Nevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant disorder characterized by tumorigenesis and physical deformities. Although more than 50 clinical manifestations have been described, only two major criteria or one major and two minor criteria are necessary for diagnosis. The most frequently observed manifestation in the oral and the maxillofacial region is an odontogenic keratocyst. In this study, we describe a 14‐year‐old boy with a diagnosis of NBCCS who presented with a central odontogenic fibroma (COF) in the mandible. This report highlights the importance of precise diagnosis and the choice of surgical method for COF.